2022
DOI: 10.1021/acs.jpclett.2c00910
|View full text |Cite
|
Sign up to set email alerts
|

Signature of Au as a Halogen

Abstract: Gold, although chemically inert in its bulk state, is reactive at the nanoscale and, in small clusters, even behaves like a hydrogen atom. Using a photoelectron spectroscopy experiment and first-principles theory, we show that Au also behaves like a halogen in small clusters. This is evident not only in strong resemblance between the photoelectron spectra of Au 2 F − and AuF 2 − but also in Au exhibiting one of the signature properties of halogens, its ability to form superhalogens with electron affinities hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 40 publications
3
8
0
Order By: Relevance
“…Here, we adopt an alternative approach to better understand UF 6 and UF 6 – by using Au as a surrogate for F. Note that the EA of the Au atom (2.32 eV) is the highest among all metals in the periodic table; it is also one of the few metals that forms ionic bonds with metal atoms, such as Cs and Th. That Au may mimic F in UF 6 is consistent with Hoffmann’s isolobal principle, which suggests that species with similar symmetry and frontier orbital energies have similar bonding and reactivity . It was previously predicted by theory that Au could behave like a halogen when interacting with U in UAu 4 . , Recent joint experimental–theory studies on various thorium–gold anions, as well as the Au 2 F molecule, have shown that indeed Au can behave very similarly to F. , In a computational pilot study of the UAuF trimer, we also found that Au mimics the chemistry of F (Section S2, and Figure S2 of the Supporting Information, SI).…”
supporting
confidence: 53%
See 1 more Smart Citation
“…Here, we adopt an alternative approach to better understand UF 6 and UF 6 – by using Au as a surrogate for F. Note that the EA of the Au atom (2.32 eV) is the highest among all metals in the periodic table; it is also one of the few metals that forms ionic bonds with metal atoms, such as Cs and Th. That Au may mimic F in UF 6 is consistent with Hoffmann’s isolobal principle, which suggests that species with similar symmetry and frontier orbital energies have similar bonding and reactivity . It was previously predicted by theory that Au could behave like a halogen when interacting with U in UAu 4 . , Recent joint experimental–theory studies on various thorium–gold anions, as well as the Au 2 F molecule, have shown that indeed Au can behave very similarly to F. , In a computational pilot study of the UAuF trimer, we also found that Au mimics the chemistry of F (Section S2, and Figure S2 of the Supporting Information, SI).…”
supporting
confidence: 53%
“…7 It was previously predicted by theory that Au could behave like a halogen when interacting with U in UAu 4 . 8,9 Recent joint experimental−theory studies on various thorium−gold anions, as well as the Au 2 F molecule, have shown that indeed Au can behave very similarly to F. 10,11 In a computational pilot study of the UAuF trimer, we also found that Au mimics the chemistry of F (Section S2, and Figure S2 of the Supporting Information, SI).…”
mentioning
confidence: 64%
“…Moreover, the experimentally determined FKrCF and FXeCF molecules and the theoretically predicted FNgCX (Ng = Kr and Xe, X = Cl, Br, and I) molecules are also found to be stable in the singlet state owing to the strong nucleophilic nature of X atoms. Therefore, a one-to-one correspondence is obtained between Au and X atoms while comparing the relative stabilities of the singlet and triplet FNgCX and FNgCM molecules, supporting the “gold-halogen” analogy. Accordingly, from now onward, we will discuss all the results for 3 FNgCCu, 3 FNgCAg, and 1 FNgCAu molecules, since they are the most stable state as per the results obtained by employing the above-mentioned high level computational calculations.…”
Section: Resultssupporting
confidence: 53%
“…Hence, the behavior of the Au atom in FNgCAu coincides well with the behavior of a halogen atom (X) in FNgCX molecules and the calculated results for FNgCX (X = Br and I) and FNgCAu molecular systems are very close to each other. The presence of strong relativistic effects in the Au atom as compared to the H, Cu, and Ag atoms drive the Au atom to behave as a better electron donor, thereby stabilizing the singlet carbene and also emphasizing on the “gold-halogen” analogy. The absence of such a behavior in hydrogen and other noble metal congeners mark a higher stability of the triplet FNgCM (M = H, Cu, and Ag) molecules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation